A simple substrate to produce the tropical epiphytic algae Hypnea pseudomusciformis - Pereira, Stefany A. [UNESP]; Kimpara, Janaina M.; Valenti, Wagner C. [UNESP] (Elsevier B.V., 2020)
The seaweeds Hypnea spp have been used as a direct human food, for carrageenan extraction, and exploitation of chemical compounds of interest. Nevertheless, its culture is still undeveloped because of difficulties in managing the epiphytic habit. Therefore, this study focuses on obtaining a suitable substrate for Hypnea pseudomusciformis settling and developing associated to a simple and efficient system to produce this red alga in tropical coastal regions of South Atlantic. We developed a substrate comprised of a 1 cm diameter polypropylene cable with 60 cm length, which was totally shredded. This structure allows that the epiphytic algae grow settled on the substrates and not only appended to it. A modular long-line structure comprised of 1m polypropylene braided cables with two substrates spaced 30 cm each. Testing the prototype in a seaweed small-farm resulted in a growth rate of 5.66 % day(-1) and a productivity of 0.64 kg m(-1) in 45 days. This simple patented technology may base used the development of the culture of H. pseudomusciformis in familiar or industrial scales.
Keywords: Seaweed; Epiphytic algae; Macroalgae; Algae farming; Mariculture